2023
DOI: 10.1021/acsami.2c20063
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Internally Hierarchical Multiphase Lattices Inspired by Precipitation Strengthening Mechanisms

Abstract: In metal metallurgy, precipitation strengthening is widely used to increase material strength by utilizing the impediment effect of the second-phase particles on dislocation movements. Inspired by this mechanism, in this paper, novel multiphase heterogeneous lattice materials are developed with enhanced mechanical properties utilizing a similar hindering effect of second-phase lattice cells on the shear band propagation. For this purpose, biphase and triphase lattice samples are fabricated using high-speed mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…The suture interface in these biological materials plays a critical role between the microscale and component size; , these biological materials can efficiently improve the load transmission and structural connection at the mesoscopic scale. ,, However, we found that the elytra load-response mechanism of the suture structure has not been fully explored. P. diabolicus usually survives when animals trample on them, and then the shell starts the self-recovery process by using stored elastic energy, which contributes to the suturing mechanism of the elytra.…”
Section: Introductionmentioning
confidence: 90%
“…The suture interface in these biological materials plays a critical role between the microscale and component size; , these biological materials can efficiently improve the load transmission and structural connection at the mesoscopic scale. ,, However, we found that the elytra load-response mechanism of the suture structure has not been fully explored. P. diabolicus usually survives when animals trample on them, and then the shell starts the self-recovery process by using stored elastic energy, which contributes to the suturing mechanism of the elytra.…”
Section: Introductionmentioning
confidence: 90%
“…Recently, biomimetic and hierarchical strategies have introduced greater complexity and functionality for microlattice structures. [3,[28][29][30][31][32][33] However, these structures described above are all characterized by the periodic arrangements of unit cells, which lead to materials with uniform mechanical responses subjected to external loads. [34] Many of these structures thus suffer from global failure modes such as coherent shear bands and fractures; they hence display fluctuating stress-strain curves without a smooth and gradual plateau.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, biomimetic and hierarchical strategies have introduced greater complexity and functionality for microlattice structures. [ 3,28–33 ]…”
Section: Introductionmentioning
confidence: 99%
“…Structures inspired by hierarchical design strategies consistently exhibited superior mechanical properties compared to traditional materials. [32,33] Therefore, developing new lattice structure configurations with high specific elastic modulus and high specific yield strength through hierarchical design strategies is of great significance for promoting the application of lightweight and high-strength lattice materials.…”
Section: Introductionmentioning
confidence: 99%